2012
DOI: 10.1603/me11110
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Molecular Investigations of Population Structure ofPhlebotomus perniciosusandPhlebotomus longicuspis(Diptera: Psychodidae) in Tunisia

Abstract: Morphological and molecular characterization of Phlebotomus (Larroussius) perniciosus Newstead and Phlebotomus (L.) longicuspis Nitzulescu in Tunisia is reported. Different localities in central and southern Tunisia were sampled. Sand flies were collected by sticky-paper traps and Center for Disease Control traps. For morphological study of males, the copulatory valves (aedeagi) were examined and the number of coxite hairs was recorded. For molecular analysis, the mitochondrial cytochrome b gene and the cytoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…The subgenus Larroussius has been well explored by inclusion of Phlebotomus ariasi (Esseghir et al, 1997;Aransay et al, 2000;Di Muccio et al, 2000;Esseghir and Ready, 2000;Franco et al, 2010;Mahamdallie et al, 2010;Bounamous et al, 2014), Phlebotomus betisi (Khadri et al, 2008), Phlebotomus chadlii (Franco et al, 2010;Bounamous et al, 2014), Phlebotomus keshishiani (Kruger et al, 2011), Phlebotomus langeroni (Booth et al, 1991;Esseghir and Ready, 2000), Phlebotomus longicuspis (Di Muccio et al, 2000;Esseghir and Ready, 2000;Pesson et al, 2004;Depaquit et al, 2005a;Boudabous et al, 2012;Bounamous et al, 2014), Phlebotomus major group (Depaquit et al, , 1999Aransay et al, 2000;Di Muccio et al, 2000;Esseghir and Ready, 2000;Absavaran et al, 2009;Parvizi et al, 2010a;Kruger et al, 2011;Latrofa et al, 2011a,b;Kasap et al, 2013), Phlebotomus orientalis (Esseghir and Ready, 2000;Seblova et al, 2013), Phlebotomus perfiliewi s. l. (Booth et al, 1991;Esseghir et al, 1997;Aransay et al, 2000;Di Muccio et al, 2000;Esseghir and Ready, 2000;Parvizi et al, 2010a;Kruger et al, 2011;Latrofa et al, 2011a,b;…”
Section: Resultsmentioning
confidence: 99%
“…The subgenus Larroussius has been well explored by inclusion of Phlebotomus ariasi (Esseghir et al, 1997;Aransay et al, 2000;Di Muccio et al, 2000;Esseghir and Ready, 2000;Franco et al, 2010;Mahamdallie et al, 2010;Bounamous et al, 2014), Phlebotomus betisi (Khadri et al, 2008), Phlebotomus chadlii (Franco et al, 2010;Bounamous et al, 2014), Phlebotomus keshishiani (Kruger et al, 2011), Phlebotomus langeroni (Booth et al, 1991;Esseghir and Ready, 2000), Phlebotomus longicuspis (Di Muccio et al, 2000;Esseghir and Ready, 2000;Pesson et al, 2004;Depaquit et al, 2005a;Boudabous et al, 2012;Bounamous et al, 2014), Phlebotomus major group (Depaquit et al, , 1999Aransay et al, 2000;Di Muccio et al, 2000;Esseghir and Ready, 2000;Absavaran et al, 2009;Parvizi et al, 2010a;Kruger et al, 2011;Latrofa et al, 2011a,b;Kasap et al, 2013), Phlebotomus orientalis (Esseghir and Ready, 2000;Seblova et al, 2013), Phlebotomus perfiliewi s. l. (Booth et al, 1991;Esseghir et al, 1997;Aransay et al, 2000;Di Muccio et al, 2000;Esseghir and Ready, 2000;Parvizi et al, 2010a;Kruger et al, 2011;Latrofa et al, 2011a,b;…”
Section: Resultsmentioning
confidence: 99%
“…longicuspis are widely distributed and sympatric in some foci, especially in the northern and central parts of the country [ 27 ]. Recently, Pesson et al [ 53 ] and Boudabous et al [ 54 ] in Morocco and Tunisia, respectively, reported a widely distribution of atypical morphs of P . perniciosus presenting single-pointed aedeagi curved at their apicies that were indistinguishable from the P .…”
Section: Discussionmentioning
confidence: 99%
“…longicuspis specimens, revealing the presence of uniquely typical morphs P . perniciosus as previously described in Tunisia [ 54 ]. Further studies with a representative number of specimens from different Algerian geographical areas could elucidate the distribution of typical and atypical forms of this sand fly species.…”
Section: Discussionmentioning
confidence: 99%
“…All male P. perniciosus collected showed atypical forms of copulatory valves. This atypical form of P. perniciosus (PNA) has been reported in northern (Pesson et al as well as in southern Morocco (Boussaa et al It was identified also in Tunisia (Ghrab et al Boudabous et al and probably in Algeria (Berchi et al Eight collected species ( S. dreyfussi, P. alexandri, P. bergeroti, S. christophersi, S. africana, P. chabaudi, P. chadlii , and P. kazeruni ) are not abundant (less than 2%) in our study area and we could not determine their distribution. For the abundant species ( S. minuta, S. fallax, P. perniciosus, P. papatasi, P. sergenti, P. longicuspis , and P. ariasi ), the geographical distribution was presented according to some environmental variables (Figure ).…”
Section: Resultsmentioning
confidence: 73%
“…This atypical form of P. perniciosus (PNA) has been reported in northern (Pesson et al 2004) as well as in southern Morocco . It was identified also in Tunisia (Ghrab et al 2006, Boudabous et al 2012 and probably in Algeria (Berchi et al 2007). Eight collected species (S. dreyfussi, P. alexandri, P. bergeroti, S. christophersi, S. africana, P. chabaudi, P. chadlii, and P. kazeruni) are not abundant (less than 2%) in our study area and we could not determine their distribution.…”
Section: Resultsmentioning
confidence: 94%